1977
DOI: 10.1111/j.1651-2227.1977.tb07952.x
|View full text |Cite
|
Sign up to set email alerts
|

Short Colon Malformation With Imperforate Anus

Abstract: Ten cases of a rare high anorectal malformation associated with short colon are presented. The significance of a large gas fluid level (occupying more than half of the abdominal cavity on invertogram) is stressed for pre-operative diagnosis. Terminal colostomy or ileostomy with disconnection of colo-vesical/colo-vaginal fistula has been considered the only adequate therapy. Associated congenital malformations have been responsible for high mortality in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 2 publications
3
43
1
Order By: Relevance
“…Interestingly, the sex ratio reported by authors outside India has been almost equal (1.27:1) while in India the reported incidence has been 3-4.3: 1. [11] In the authors series (152 cases, 1992-2005), it was significantly higher in males than in females (7:1)…”
Section: Map Of Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the sex ratio reported by authors outside India has been almost equal (1.27:1) while in India the reported incidence has been 3-4.3: 1. [11] In the authors series (152 cases, 1992-2005), it was significantly higher in males than in females (7:1)…”
Section: Map Of Indiamentioning
confidence: 99%
“…[10] The condition is defined as an anomaly in which all or part of the colon is replaced by a pouch-like dilatation The first report from India came in 1972 by Singh and that communicates distally with the urogenital tract by a Pathak who in a series of six cases, named this condition A supralevator anorectal anomaly is as "short colon" and attempted to discuss its associated with a colonic pouch of variable size (5-15 cm embryogenesis. [11] Gopal in 1978 called it colonic reservoir in diameter). This condition has now been included in a case with Rectovaginal fistula.…”
mentioning
confidence: 99%
“…The Indian literature is replete with the different surgical techniques. Since CPC was first reported by Professor IC Pathak in 1972 [1] there are large series of CPC with reviews and evaluations of various surgical procedures [11][12][13][14]. [19].…”
Section: Type IImentioning
confidence: 99%
“…Intrauterine vascular accidents, obliteration of inferior mesenteric artery or part of it and factors like pesticides, geographic environment, climate, economic and cultural status, are believed to be factors responsible for ARM. However, recent reports in the literature have shown that the germ line mutations/ deletions of genes encoding the proteins of the signaling pathways responsible for normal colon result in its malformations in experimental studies [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Management of pouch colon is controversial with very poor final result and outcome. Classical management options include initial management with a) diversion (window colostomy/proximal colostomy/ileostomy) with or without division of fistula, b) excision of the pouch and end colostomy after division of fistula, and c) coloplasty and end colostomy.…”
Section: Introductionmentioning
confidence: 99%